2009
DOI: 10.1007/s10681-009-9964-x
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of class I SSR markers targeting (GATA) n repeat motifs in rice

Abstract: SSR markers targeting (GATA) n motifs are known to be highly polymorphic and useful in many organisms. (GATA) n motif specific SSR markers covering the whole rice genome are not available. The present study was carried out with an objective to identify class I rice microsatellites in the rice genome with (GATA) n motifs, in-silico, and validate their potential as molecular markers. A total of 243 such motifs were identified; 65 of these were present in the genic region, 59 were in the upstream region and the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Markers with PIC values of 0.5 or above are broadly highlights for the genetic studies since they are most useful in describing the polymorphism magnitude of a specific locus (Akkaya and Buyukunal Bal 2004). The obtained results are showing close resemble to the output mentioned by Brondani et al 2008, Rajendrakumar et al 2009and Matin et al 2012; they also mentioned mean PIC Values of 0.61, 0.61 and 0.634, respectively with variable set of rice genotypes with use of SSR markers. However, the PIC values reported in this study were lower than those obtained by Sonkar et al 2016 who reported a mean PIC value of 0.92.…”
Section: Shikha Tripathi Et Alsupporting
confidence: 86%
“…Markers with PIC values of 0.5 or above are broadly highlights for the genetic studies since they are most useful in describing the polymorphism magnitude of a specific locus (Akkaya and Buyukunal Bal 2004). The obtained results are showing close resemble to the output mentioned by Brondani et al 2008, Rajendrakumar et al 2009and Matin et al 2012; they also mentioned mean PIC Values of 0.61, 0.61 and 0.634, respectively with variable set of rice genotypes with use of SSR markers. However, the PIC values reported in this study were lower than those obtained by Sonkar et al 2016 who reported a mean PIC value of 0.92.…”
Section: Shikha Tripathi Et Alsupporting
confidence: 86%
“…2005, Glaszman 1987) which underscores the potentiality of hypervariable microsatellite markers (hvRMs) in studying genetic relatedness within and between species. Very recently, Rajendrakumar et al. (2009) proved that (GATA)n repeats of Class I SSR markers could be effectively used for genetic diversity studies and marker‐assisted selection.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the pattern of grouping clearly corresponds to earlier reports (Garris et al 2005, Glaszman 1987) which underscores the potentiality of hypervariable microsatellite markers (hvRMs) in studying genetic relatedness within and between species. Very recently, Rajendrakumar et al (2009) proved that (GATA)n repeats of Class I SSR markers could be effectively used for genetic diversity studies and marker-assisted selection. However, the present study offers experimental evidence for the potential use of evenly spaced hvRMs in marker-assisted selection/breeding and in genetic diversity analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The SSR markers are particularly suitable for evaluating genetic diversity and relationships among plant species, populations, or individuals (Kostova et al 2006;Tu et al 2007), studying rice germplasm for either conservation or utilization (Sharma et al 2007); marker-assisted selection breeding (Perez-Sackett et al 2011;Rani and Adilakshmi 2011); cultivar identification; hybrid purity analysis and gene mapping studies (Weising et al 1997;Altaf-Khan et al 2006;Rajendrakumar et al 2009;Sarao et al 2010). …”
Section: Introductionmentioning
confidence: 99%